Culture and Technology: Genesis and Status of a Research Initiative - Banse, Gerhard; Hauser, Robert (Teorie vědy / Theory of Science, 2010)
The systematic and interdisciplinary study of relations between technology and culture is at the core of one project at the Karlsruher Institute of Technology (KIT). This text introduces the institutional background of this project as well as some early ac-tivities and first results. After that it focuses on the theoretical foundations for the concepts of technology and culture being used in this project. Based on these thoughts the correlation between technology and culture is being illustrated and some examples of its interdependencies are given. Finally some concluding theses are presented.